„Nie trzeba było domu palić, tylko Żydów wyprowadzić i pozabijać” - Bikont, Anna (Zagłada Żydów. Studia i Materiały, 2011)
“Why, There Was No Need to Burn the House, It Was Enough to Escort the Jews out and Kill Them.” Postscript to Jerzy Mazurek and Alina Skibińska’s „Nie trzeba było domu palić, tylko Żydów wyprowadzić i pozabijać”. Postscriptum do tekstu Jerzego Mazurka i Aliny Skibińskiej „Barwy Białe” w drodze The author visited the villages and towns where the murders of Jews hiding in the Kielce region after the liquidation of the ghettos took place (the acts were described in Jerzy Mazurek and Alina Skibińska’s text published in this volume). Only a small number of inhabitants, who were there during the war, remains, but the memory of the murdered Jews is still present. Both the memory of those killed by the passing Home Army detachment (and who were buried by the locals who were ordered to do so) and the memory of those denounced by the locals, killed on the spot or escorted to a German police station. Memory does not always entail compassion. The article proves that field research, even one conducted so many years after the Holocaust, can introduce additional knowledge into historical research.